Cardiovascular and renal outcomes with empagliflozin in heart failure - Packer, Milton; Anker, Stefan D.; Butler, Javed; Filippatos, Gerasimos; Pocock, Stuart J.; Carson, Peter; Januzzi, James; Verma, Subodh; Tsutsui, Hiroyuki; Brückmann, Martina; Jamal, Waheed; Kimura, Karen; et al. (The New England journal of medicine, 2020)
Among patients with heart failure and a reduced ejection fraction, those who received the SGLT2 inhibitor empagliflozin had a significantly lower incidence of cardiovascular death or hospitalization for heart failure than those who received placebo.